Dampak Kepemimpinan Pemberdayaan, Modal Sosial, dan Program Keberlanjutan terhadap Kesejahteraan Masyarakat Jangka Panjang: Sebuah Studi Tinjauan Literatur Sistematis - Muhammad Kamal; Abdul Wahab Hasyim; Nahu Daud; Rahmat Sabuhari (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
Capturing the breadth of research on social capital, empowering leadership, sustainable initiatives, and community welfare is the goal of this systematic literature analysis. Five publications that satisfied the inclusion requirements were found after a thorough search of the Scopus and Web of Science (WoS) databases using PRISMA, which was done between January 2010 and November 2024. The compilation of these articles demonstrates that social capital, sustainable programs, and community welfare have been primarily studied in the healthcare industry. Furthermore, research findings were also conducted in African countries, Turkey, Italy, Canada, and various other countries. Furthermore, the research methods employed were predominantly qualitative. Future research directions are also provided, along with theoretical and practical contributions.